Leprosy of Lucio - Montoya Fernández, Raúl (1960)
Among a group of 472 patients with lepromatous leprosy, we observed five acsos (1.06%) leprosy of Lucio, 3 of them in primary diffuse nodular lepromatous and 2. In all cases we tested the acute onset of vesicular-peptic elements hemorrhagic-necrotic (Lucio phenomenon) and hypersensitivity to lepromin 6 hours (Medina phenomenon). The histological findings have shown, throughout, a leper periartresis with nonspecific necrotizing vasculitis, which is the typical histological appearance of Lucio phenomenon. In three of the outbreaks reactional type Lucio, average duration of 185 days have been the only reaction expression; in 2 of them have been grafted onto a common reaction type rash; in some outbreaks were repeated. The sulfonic treatment wiped out the few months Lucio syndrome.